Searching of biomechanical determination factor for improving club head speed during the driver swing in male golf players - Lee, J.-W.; Kim, Y.-S.; Park, J.-S. (Korean Journal of Sport Biomechanics, 2024)
Objective: The aim of this study was to identify the biomechanical determination factor for improving club head speed during the driver swing in male golf players. Method: Twenty-seven golf players were participated in this study. Eight motion capture cameras (250 Hz) and two force plates (2,000 Hz) were used to collect peak angular velocity and ground reaction force data. It was performed stepwise multiple linear regression analysis and alpha set at .05. Results: The peak plantar flexion angular velocity of the left ankle joint and the peak adduction angular velocity of the right shoulder joint were statistically significant. The peak plantar flexion angular velocity of the left ankle joint and the peak adduction angular velocity of the right shoulder during downswing. Conclusion: It is suggested that applying body conditioning training aimed at improving related body functions to increase maximum plantar flexion angular velocity in the left ankle joint will be effective in improving club head speed.